PENENTUAN NILAI TEBAL PARUH (HVL) PADA CITRA DIGITAL COMPUTED RADIOGRAPHY - Cicilia Artitin; Suryono Suryono; Evi Setiawati (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Half value layer (HVL) can be determined by using the method of digital image processing. This research is done by using stepwedge as an object. The stepwedge exposed a tube voltage of 80 kV and 10 mAs, 20 mAs, 30 mAs, 40 mAs, and 50 mAs. After getting the next image is processed in Matlab to find the value of gray level and HVL value . HVL values generated in this study was 3.08 mmAl, mmAl 3.60, 5,67mmAl, mmAl 7,27, and 8,41 mmAl. HVL value is still allowed under the Indonesian republic health minister's decision no. 1250, 2009, requirements on the voltage value of 80 kV HVL better when ≥ 2.3 mmAl. The value for examination was stated in Regulation No. Head BAPETEN 9 of 2011 so that the X-ray plane fit for use . Keywords: Half Value Layer (HVL), Stepwedge, Grey Level, Digital Image